2007
DOI: 10.1080/00173130701472181
|View full text |Cite
|
Sign up to set email alerts
|

Walls of allergenic pollen: Special reference to the endexine

Abstract: Allergic rhinitis is an increasing health problem and pollen allergens are amongst the main elicitors of hay fever symptoms. Allergenic pollen contains a set of differently allergenic proteins which are thought to play a role in the pollen germination and fertilisation process. They are released upon contact with the stigma or mucosa or upon pollen grain rupture. Although the determinants of allergenicity of these proteins are still largely undiscovered, accessibility and solubility are now thought to mainly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 60 publications
(95 reference statements)
1
19
0
1
Order By: Relevance
“…Used in a 1% aqueous solution of potassium permanganate, it particularly stains the endexine producing a distinct contrast. This has been confirmed for many species (Ulrich, 2006;Diethart et al, 2007). The application of different TEM staining techniques for one and the same sample is very important and highly recommended in order to avoid misinterpretations in the pollen wall architecture.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Used in a 1% aqueous solution of potassium permanganate, it particularly stains the endexine producing a distinct contrast. This has been confirmed for many species (Ulrich, 2006;Diethart et al, 2007). The application of different TEM staining techniques for one and the same sample is very important and highly recommended in order to avoid misinterpretations in the pollen wall architecture.…”
Section: Discussionmentioning
confidence: 87%
“…A morphological feature of the endexine is its increasing thickness closer to the aperture. According to Hesse et al (2009), the endexine may be compact, as in Oenothera (Takahashi & Skvarla, 1990), spongy, as in several Araceae (Weber et al, 1999) or lamellar as seen in Ambrosia (Diethart et al, 2007), Brasenia (Taylor & Osborn, 2006) and in many gymnosperm taxa (Kurmann, 1990(Kurmann, , 1994. The endexine has a distinct substructure including laterally oriented white line-centred lamellations (Rowley, 1988(Rowley, , 1995.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En el grano de polen maduro se observó que la pared carece de endexina y corresponde al tipo III de la clasificación de Walker & Doyle (1975). Esto concuerda con observaciones de granos de polen de otras especies de cereales, tales como Triticum aestivum L., Secale cereale L., Zea mays L. y Avena sativa L. (Diethart et al 2007).…”
Section: Discussionunclassified
“…Specific staining with potassium permanganate showed that endexine contains phospholipid-protein complexes (Diethart et al, 2007;Weber & Ulrich, 2010), a fact that emphasises the similarity of plasma membrane and initial endexine lamellae (lamellar micelles).…”
Section: Development Of Endexinementioning
confidence: 99%